Qaraqalpaq tilin avtomatik túrde analizlewde mashinalıq oqıtıw algoritmlerin qollanılıw (SCIENCE and SOCIETY, 2025)
This article explores the application of machine learning algorithms for the automatic analysis of the Karakalpak language. It describes the processes of automated analysis, including morphology, syntax, and semantics, and examines the technical capabilities of the algorithms. The creation and analysis of language corpora using Python